The effect of postoperative positive end-expiratory pressure on postoperative bleeding after off-pump coronary artery bypass grafting - Yildiz, Yahya (Arch Med Sci, 2014)
INTRODUCTION: To compare postoperative prophylactic use of two positive end-expiratory pressure (PEEP) levels in order to prevent postoperative bleeding in patients undergoing off-pump coronary artery bypass grafting (CABG) surgery. MATERIAL AND METHODS: Sixty patients undergoing an elective off-pump CABG operation were included in this prospective, nonrandomized clinical trial. Patients were divided into two groups as receiving either 5 cm H(2)O (group 1) or 8 cm H(2)O PEEP (group 2) after the operation until being extubated. Chest tube outputs, use of blood products and other fluids, postoperative hemoglobin levels, accumulation of pleural and pericardial fluid after the removal of chest tubes, and duration of hospital stay were recorded and compared. RESULTS: Low- and high-pressure PEEP groups did not differ with regard to postoperative chest tube outputs, amounts of transfusions and crystalloid/colloid infusion requirements, or postoperative hemoglobin levels. However, low-pressure PEEP application was associated with significantly higher pleural (92 ±37 ml vs. 69 ±29 ml, p = 0.03) and pericardial fluid (17 ±5 ml vs. 14 ±6 ml, p = 0.04) accumulation. On the other hand, high-pressure PEEP application was associated with significantly longer duration of hospitalization (6.25 ±1.21 days vs. 5.25 ±0.91 days, p = 0.03). CONCLUSIONS: Prophylactic administration of postoperative PEEP levels of 8 cm H(2)O, although safe, does not seem to reduce chest-tube output or transfusion requirements in off-pump CABG when compared to the lower level of PEEP. Further studies with larger sample sizes are warranted to confirm the benefits and identify ideal levels of PEEP administration in this group of patients.